Effect of HSV-2 Serostatus on Acquisition of HIV by Young Men: Results of a Longitudinal Study in Orange Farm, South Africa - Sobngwi-Tambekou, Joelle; Taljaard, Dirk; Lissouba, Pascale; Zarca, Kevin; Puren, Adrian; Lagarde, Emmanuel; Auvert, Bertran (The Journal of infectious diseases, 2009)
BackgroundThe objectives of this study were to assess the impact among young men of herpes simplex virus type 2 (HSV-2) status on the acquisition of human immunodeficiency virus (HIV) and on the protective effect of male circumcision against HIV acquisition MethodsWe used data collected during a male circumcision trial conducted in Orange Farm, South Africa. We estimated adjusted incidence rate ratios (IRRs) for HIV acquisition, using survival analysis and background characteristics, HSV-2 status, male circumcision status, and sexual behavior as covariates ResultsCompared with subjects who remained HSV-2 negative throughout the study, subjects who were HSV-2 positive at enrollment had an adjusted IRR of 3.3 (95% confidence interval [CI], 1.5–7.4; P=.004), and those who became HSV-2 positive during follow-up had an adjusted IRR of 7.0 (95% CI, 3.9–12.4; P<.001). The population fraction of incident HIV infection attributable to HSV-2 was 27.8% (95% CI, 17.7%–37.2%). Intention-to-treat analysis of the protective effect of male circumcision on HIV acquisition was the same among men with and men without HSV-2 (0.38 vs. 0.37; P=.93) ConclusionsThis study shows that HSV-2 has a substantial impact on HIV acquisition among young South African men. It suggests that HSV-2 infection enhances HIV acquisition and is responsible for ∼25% of incident cases of HIV infection. However, the protective effect of male circumcision against HIV acquisition appears independent of HSV-2 serostatus Trial registrationClinicalTrials.gov identifier: NCT00122525